2020
DOI: 10.3892/ijmm.2020.4496
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarein inhibits the development of colon cancer via CDC4‑mediated RAGE ubiquitination

Abstract: Scutellarein has been identified to serve an anti-tumor function in human colon cancer, but the underlying mechanisms remain largely unclear. The present study further investigated the effect and mechanism of scutellarein, extracted from wild chrysanthemum, in the progression of colon cancer. MTT, clone formation, flow cytometry and tumor-bearing mice assays were used to detect cell viability, clone formation, apoptosis and tumorigenesis, respectively. Western blot and quantitative PcR assays were performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…As shown in many studies mentioned in this review investigating the role of RAGE by its blockage through siRNA and antibodies and antagonists treatment, RAGE activation stopped, as well as underlying mechanisms leading to tumorigenicity. Also, it has been indicated that antibodies against RAGE ligands can decrease the risk of CRC (178)(179)(180)(181)(182). This, as mentioned before, the effect of prolonged RAGE blockade in human subjects is important because RAGE plays vital roles in normal physiology.…”
Section: Therapeutic Strategies Against Rage In Crcmentioning
confidence: 81%
“…As shown in many studies mentioned in this review investigating the role of RAGE by its blockage through siRNA and antibodies and antagonists treatment, RAGE activation stopped, as well as underlying mechanisms leading to tumorigenicity. Also, it has been indicated that antibodies against RAGE ligands can decrease the risk of CRC (178)(179)(180)(181)(182). This, as mentioned before, the effect of prolonged RAGE blockade in human subjects is important because RAGE plays vital roles in normal physiology.…”
Section: Therapeutic Strategies Against Rage In Crcmentioning
confidence: 81%
“…Also, Gu et al found that quercetin may be a promising therapeutic avenue for SARS-CoV-2 injury-induced AKI [ 39 ]. Scutellarein is a flavonoid monomer that has been demonstrated to exert various pharmacological effects including anticancer [ 40 ], anti-inflammatory [ 41 ], and antifibrosis activities [ 42 ]. Furthermore, a recent study found that diosmetin also has renoprotective effects in the sepsis-induced AKI model by activating the TUG1/Nrf2/HO-1 pathway [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can exert anti-inflammatory, anti-oxidant, and anti-cancer effects ( Kang et al, 2020 ). Scutellarein is a flavone present in huangqin which can exert a higher bioavailability compared with scutellarin ( Li et al, 2020c ). Helicase protein is also served as a potential target for the development of anti-HCoV (human coronavirus) preparations.…”
Section: The Anti-novel Coronaviral Compound From Tcm—anti-inflammatory Responsesmentioning
confidence: 99%